THE URGENCY OF THE PROSECUTOR'S ROLE IN HANDLING CONFISCATED AND CONFISCATED GOODS FROM THE STATE (CASE STUDY OF THE BATAM DISTRICT PROSECUTOR'S OFFICE) - Simbolon, Melati Meliana; Tri Bawono, Bambang (Jurnal Hukum Khaira Ummah, 2024)
This study highlights the importance of the role of the Prosecutor's Office in managing confiscated and seized state assets. These assets are very crucial and must be managed effectively to support the law enforcement process as well as increase state revenue. Unfortunately, various obstacles such as lack of coordination between institutions, limited use of information technology, and the need to increase human resource capacity are still major challenges in the implementation process. Through an empirical legal approach and descriptive analysis methods, this study evaluates the implementation and weaknesses in the management of confiscated assets at the Batam District Attorney's Office, and examines the important role of the prosecutor's office in this regard.